THE ROLE OF MIRNAS IN TYMORIGENESIS.LITERATURE REVIEW. - I.S. Brodetskyi (Український стоматологічний альманах, 2019)
Introduction. There are many diagnostic techniques in modern medicine, that enable preoperative and postoperative human neoplasms verification (identification).There are a number of postoperative diagnostic techniques, namely his to pathological, immunohistochemical and genetic one. The last-mentioned is rather popular. One of the genetic approaches in tumor diagnostics is the examination of the role of microRNA molecules.